From Plug to Planet: Market dynamics behind Energy efficient Home Appliances (International Journal of Food and Nutritional Sciences, 2022)
Worldwide, the household-appliance sector is undergoing three clear shifts: (1) rising residential energy consumption, (2) Rapid technological upgrades in appliance design, and (3) An accelerating push toward energy-sustainability solutions. Electrical home appliances are at the centre of these trends